Comparison of General-Social Health and Corona-Induced Anxiety Between Active and Inactive Students in the COVID-19 Pandemic - Ahmadabadi, Somayeh (Frontiers in Psychiatry, 2021)
Background General health includes physical and mental health and their interactions, and physical activity can improve people’s mental and social health. The present study has compared general-social health and COVID-19-induced anxiety between active and inactive students during the COVID-19 -19 pandemic. Methods A causal-comparative research design was used in this study. The statistical population consisted of all students of the Farhangian University of Mashhad (2500 students) in 2020, out of whom 752 students were randomly selected (323 men and 429 women). Subjects were assessed for general health, social health, and COVID-19-induced anxiety. Data normality was investigated by the Kolmogorov-Smirnov test and data were analyzed statistically using independent t-test and Pearson correlation coefficient test. Results The results of the present study showed that there was a significant difference between general health and COVID-19-induced anxiety of active and inactive students (p = 0.001), but no significant difference was observed between these two groups in social health (p≥0.05). Results obtained regarding the correlation indicated that there was a significant correlation between general and social health in both active and inactive students (p = 0.001). However, there was no significant correlation between COVID-19-induced anxiety and general-social health (p≥0.05). Conclusion According to the results of the present study, it can be said that an active lifestyle and physical activity are important factors to improve general health and reduce anxiety, especially in specific conditions of the COVID-19 outbreak. Therefore, it is recommended that students have a regular exercise program to reduce their anxiety and increase the level of their physical health.